Examination of Escherichia coli O157:H7 and some Virulence Genes in Marketed Minced Meat Samples - Kalin, Recep; Ongor, Hasan (Kafkas Univ, Veteriner Fakultesi Dergisi, 2014)
In this study, the presence of Escherichia coli (E. coli) O157:H7 was investigated in minced meat samples. E. coli O157:H7 was detected in six (7.5%) of the minced meat samples. Examination of the positive isolates for the presence of virulence genes; stx1 was determined in one isolate, stx2 in three isolates and both stx1 and stx2 were found in one isolate. Also eae genes were observed in all the positive isolates.
Tüketime sunulan kıymalarda Escherichia coli O157:H7’nin ve bazı virülens genlerinin araştırılması
Keywords: E. coli O157:H7; Minced meat; PCR